Laços e gerações: um estudo sobre velhos(as) de Santa Maria/RS e sua condição de sujeito - Duarte, Lilian (Universidade do Vale do Rio do Sinos, 2008)
In this research it presents an empirical study on the present condition of the elderly of the city of Santa Maria/ RS, as being part of an analysis that passes by the topics of the aging process through consideration of daily social roles, the relations in the family environment and intergenerational, of life after work and, finally, the subject’s condition of the elderly in the contemporaneity. That circumstance was approached through two perspectives: the subject under the social determinations (Sociological perspective) and the subject of experience (Social psychology perspective). Starting with an initial collection of information (appendix I) referring to the social situation of the elderly in Santa Maria, RS, it has searched for, through interviews and life story speech (appendix II) and later analysis, identifying and understanding the amplitude and the complexity of everyday living situations of being elderly: the notion of that population about what is, for them, to be old and the emphatic relatio
Keywords: envelhecimento; modernidade; papéis sociais; Santa Maria/RS; idosos; modernity; social roles; elderly; Ciências Sociais Aplicadas